Winter mesoscale variations of carbonate system parameters and estimates of CO2 fluxes in the Gulf of Cadiz, northeast Atlantic Ocean (February 1998) - Santana-Casiano, J. Magdalena; González-Dávila, Melchor; Dafner, Evgeny V. (Journal of Geophysical Research, 2018)
Further observations with small spatial and temporal resolutions conducted during different seasons are required in order fully to understand the role that shelves play in the global carbon cycle. The components of the carbonate system (total alkalinity, pH in the total scale, total dissolved inorganic carbon, and CO2 fugacity), and dissolved oxygen, nutrients, and phytopigments were studied along the mesoscale section over the continental shelf and slope in the Gulf of Cadiz in February 1998. All the chemical properties clearly distinguish four different water masses: Gulf of Cadiz Water, North Atlantic Surface Water, North Atlantic Central Water, and Mediterranean Water. From the thermohaline properties and applied chemical conservative tracers for each water mass, a mixing model has been established which explains more than 96% of the variability in the distribution of chemical properties. The relative variation of nutrients and carbon concentrations resulting from the regeneration of organic matter was estimated. The contribution of Mediterranean water to the waters at the traverse of Cadiz varies from 15% to 40% according to this model. The difference of fCO2 between seawater and atmosphere (ΔfCO2 = −35 μatm) shows that the surface seawater in the Gulf of Cadiz is a sink for atmospheric CO2 during winter with an average calculated net CO2 flux across the air‐sea interface of about −19.5 ± 3.5 mmol m−2 d−1. We estimate that at the traverse of Cadiz the shallow core of Mediterranean outflow carries out 1.2 • 104 to 2.4 • 104 mol inorganic carbon s−1. This estimate is 1 order of magnitude lower than that calculated for the Mediterranean outflow in the Strait of Gibraltar. 11 2,992 Q1